2015
DOI: 10.1515/chempap-2015-0237
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phytochemicals and antioxidant capacity of selected Eucalyptus species using conventional extraction

Abstract: Eucalyptus species have found their place in traditional medicine and pharmacological research and they have also been shown to possess a large number of phenolic compounds and antioxidants. The present study sought to implement conventional extraction to yield maximal total phenolic content (TPC), total flavonoid content (TFC), proanthocyanidins, antioxidants, and saponins from E. robusta using different solvents. The most suitable extraction solvent was further employed for extracting phytochemicals from E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…In the present study, all the tested eucalypts showed a higher saponin content compared to E . microcorys extract reported earlier …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…In the present study, all the tested eucalypts showed a higher saponin content compared to E . microcorys extract reported earlier …”
Section: Resultsmentioning
confidence: 64%
“…microcorys, and E . globulus when conventional extraction was employed . In the present study, TPC of aqueous A .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The findings of Goli et al revealed that the level of phenolic compounds from pistachio ( Pistachia vera ) hulls obtained by conventional solvent extraction (either in water or in methanol) was as high as ultrasound‐assisted extraction and approximately 5 times higher than supercritical fluid extraction. Moreover, total phenolic content (TPC) of Eucalyptus robusta aqueous extract achieved using conventional extraction was approximately 2.5‐fold higher than that using microwave‐assisted extraction . Hence, this study employed RSM to optimize the conventional extraction process, which is a simple and up‐scalable extraction method to extend to commercial production scale, to obtain the highest levels of phenolics, flavonoids, and antioxidant power within H. hirsuta L. Further, as extraction solvents play an important role for bioactive compound extraction within plant materials, preliminary experiments determined 40% (v/v) methanol to be the solvent of choice and was used throughout the study.…”
Section: Introductionmentioning
confidence: 99%